An Evaluation of the Teaching Aids Used By English Teachers within Libyan Secondary Schools - Gadour, Abdelbasit; Samia Amaniana (Britain International for Academic Research (BIAR) Publisher, 2015)
This study is concerned with the English language teachers' views regarding the use of teaching aids in secondary schools in Libya. The aim is to explore English teachers’ opinions of the availability, problems, sources and other characteristics of the teaching aids. In order to explore these issues, this study has made use of a combination of methods in the form of questionnaire and interview with English language teachers. One hundred questionnaires were sent to English teachers in secondary schools in Libya, of whom 85 responded. This was followed by interviews with some teachers. Although the results of this study echoed the general views on the importance of using teaching aids, it revealed that traditional teaching aids e.g. chalk and blackboard, pictures and textbooks still dominate. Apparently more teaching aids are used by English teachers in private schools than in state schools, yet teachers seemed to have common issues preventing them from using teaching aids which include: lack of money to purchase aids, lack of locally produced aids, students' language inadequacy, insufficient time, and class size. The findings of this study reflect the urgency to address these problems including that of the English curriculum in secondary schools.